Vitamin D(3) supplementation for 16 weeks improves flow-mediated dilation in overweight African American adults - Harris, Ryan A (2011)
BACKGROUND: A growing body of evidence has linked vitamin D deficiency to increased risk of cardiovascular disease. Vitamin D deficiency is also more common in African Americans for whom an increased cardiovascular disease risk exists. This study sought to test the hypothesis that 16 weeks of 60,000 IU monthly supplementation of oral vitamin D(3) would improve flow-mediated dilation (FMD) in African Americans, whereas no change would be observed in the placebo group. METHODS: A randomized, double blind, placebo controlled clinical trial was conducted. Fifty-seven African American adults were randomly assigned to either the placebo group or vitamin D group. RESULTS: Following 16 weeks of placebo (n=23; mean age 31±2 years) or 60,000 IU monthly oral vitamin D(3) (n=22; mean age 29±2 years), serum concentrations of 25 hydroxyvitamin D increased from 38.2±3.0 nmol/L to 48.7±3.2 nmol/L and 34.3±2.2 nmol/L to 100.9±6.6 nmol/L, respectively. No changes in serum parathyroid hormone, serum calcium, or urine calcium/creatinine were observed following either treatment. Following 16 weeks of treatment, significant improvements in FMD were only observed in the vitamin D group (1.8±1.3%), whereas the placebo group had no change (-1.3±0.6%). Similarly, the vitamin D group exhibited an increase in absolute change in diameter (0.005±0.004 cm) and FMD/shear (0.08±0.04 %/s(-1), AUC × 10(3)) following treatment, whereas no change (-0.005±0.002 cm and -0.02±0.02 %/s(-1), AUC, respectively) was observed following placebo. CONCLUSIONS: Supplementation of 60,000 IU monthly oral vitamin D(3) (~2000 IU per day) for 16 weeks is effective at improving vascular endothelial function in African American adults.